Long-Term Follow-Up After Catheter Ablation of Atrioventricular Nodal Reentrant Tachycardia in Children. (November 2016) - Backhoff, David; Klehs, Sophia; Müller, Matthias J.; Schneider, Heike E.; Kriebel, Thomas; Paul, Thomas; Krause, Ulrich
Abstract : Background—: Catheter ablation of the slow conducting pathway (SP) is treatment of choice for atrioventricular nodal reentrant tachycardia (AVNRT). Although there are abundant data on AVNRT ablation in adult patients, little is known about the long-term results ≥3 years after AVNRT ablation in pediatric patients. Methods and Results—: Follow-up data from 241 patients aged ⩽18 years who had undergone successful AVNRT ablation were analyzed. Median age at ablation had been 12.5 years, and median follow-up was 5.9 years. Radiofrequency current had been used in 168 patients (70%), whereas cryoenergy had been used in 73 patients (30%). Procedural end point of AVNRT ablation had been either SP ablation (no residual dual atrioventricular nodal physiology) or SP modulation (residual SP conduction allowing for a maximum of one atrial echo beat). After the initial AVNRT ablation, calculated freedom from AVNRT was 96% at 1 year, 94% at 3 years, 93% at 5 years, and 89% at 8 years. Age, sex, body weight, the choice of ablation energy, and the procedural end point of AVNRT ablation did not impact freedom from AVNRT. Six of 22 AVNRT recurrences (27%) occurred ≥5 years after ablation. No late complications including atrioventricular block were noted. Conclusions—: Cumulatively, catheter ablation of AVNRT continued to be effective in >90% of our pediatric patients during the long-term course. A significant part of recurrences occurred >5 years post ablation. Body weight, energy source, and the end point of ablation had no impact on long-term results. No adverse sequelae were noted.